Analisis Perbandingan Strategi Pemasaran Secara Online Dan Offline Pada UMKM Dewfh Dimsum Di Sidoarjo - Falimatus Mei Lia; Khofifah Nur Aini; Selly Aprilia; Maulida Zakiyatuz Zuhria; Sonja Andarini; Indah Respati Kusumasari; Sabeta Putri Ramadhani (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze and compare the effectiveness of online and offline marketing stratgeies implemented by UMKM Dewfh Dimsum in Sidoarjo. In facing increasingly competitive market competition, Dwefh Dimsum combines both marketing approaches to reach consumers more widely. This study uses a descriptive qualitive method with data collection techniques through interviews, observations, and documentation. The results of the study indicate that online marketing strategies excel in terms of wide market reach and cost efficiency, while offline strategies are more effective in building personal relationships and customer loyalty. The combination of the two has proven to be an optiomal approach in improving the performance of UMKM business. The findings provide insight for culinary enterpreneurs in designing adaptive and responsive marketing strategies to market dynamics in the digital era.